Analisis Strategi Pemasaran dalam Meningkatkan Penjualan Lilin pada Perusahaan CV. Arrifa Studi Kasus di Kota Tasikmalaya - Indangayu Surihutami; Aldy Santo Hegiarto (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the marketing strategies implemented by CV. Arrifa to increase candle sales in Tasikmalaya City. This research focuses on four main elements of the marketing mix: product, price, distribution (place), and promotion. The method used is descriptive qualitative with a case study approach. Data collection techniques included in-depth interviews, direct observation, and field documentation to obtain relevant and comprehensive data.The results show that, in terms of product, CV. Arrifa markets two main types of candles: regular candles and super candles, which are widely used by the public as alternative lighting sources during power outages. The company focuses on the quality of raw materials and flame durability as its main competitive advantages. In terms of pricing, CV. Arrifa sets prices based on market segmentation and product type, and provides pricing flexibility for large-volume purchases or repeat customers. Its distribution strategy remains conventional, through direct sales by a sales team that regularly visits stores, without utilizing digital platforms or online marketplaces. In terms of promotion, CV. Arrifa relies on personal networks, word-of-mouth, special pricing, and the distribution of free product samples to attract new customers. Despite facing challenges such as declining sales due to the emergence of alternative products such as emergency lights, the number of new customers continues to increase due to consistent promotions. However, the company has not yet optimally utilized digital technology in its marketing activities, and sales recording is still done manually. In conclusion, CV. Arrifa needs to innovate its marketing strategy, particularly through the use of digital technology, to increase its competitiveness and expand its market reach amidst increasingly competitive industry conditions.